Benign gynecologic conditions are associated with ovarian cancer risk in African-American women: A case-control study - Park, Hyo K. (Cancer Causes Control, 2018)
BACKGROUND: The association between common benign gynecologic conditions and ovarian cancer remains under-studied in African Americans. Therefore, we examine the association between self-reported history of benign gynecologic conditions and epithelial ovarian cancer risk in African-American women. METHODS: Data from a large population-based, multi-center case-control study of epithelial ovarian cancer in African-American women were analyzed to estimate the association between self-reported history of endometriosis, pelvic inflammatory disease (PID), fibroid, and ovarian cyst with epithelial ovarian cancer. Logistic regression was used to calculate odds ratios (OR) and 95% confidence intervals (CI) for the associations between individual and composite gynecologic conditions and ovarian cancer. RESULTS: 600 cases and 752 controls enrolled in the African American Cancer Epidemiology Study between December 1, 2010 and December 31, 2015 comprised the study population. After adjusting for potential confounders, a history of endometriosis was associated with ovarian cancer (OR 1.78; 95% CI 1.09–2.90). A non-significant association of similar magnitude was observed with PID (OR 1.33; 95% CI 0.82–2.16), while no association was observed in women with a history of fibroid or ovarian cyst. A positive trend was observed for an increasing number of reported gynecologic conditions (p=0.006) with consistency across histologic subtypes and among both oral contraceptive users and non-users. CONCLUSION: A self-reported history of endometriosis among African-American women was associated with increased risk of ovarian cancer. Having multiple benign gynecologic conditions also increased ovarian cancer risk.